Gender dan Problematika Ekonomi Perempuan Aceh - Iskandar, Iskandar (Pusat Studi Gender dan Anak - PSGA (Center for Gender and Child Studies) Institut Agama Islam Negeri Lhokseumawe, Aceh, 2022)
Globalization presents complex challenges for women worldwide, accentuating gender biases and prompting inquiries into their societal roles. In Aceh, women hold pivotal positions in fostering progress and maintaining social stability. This qualitative study employs descriptive survey techniques to investigate the status of women in Aceh. The research entails various stages, including data collection from diverse informants, subsequent data reduction, and analysis. Findings underscore the necessity of redefining perceptions of women in Aceh and restructuring their domestic and public rights with sensitivity. Empirical evidence highlights the significant contributions of Acehnese women to the region's social, cultural, and economic advancement. Therefore, it is imperative to recognize and appreciate their roles amidst globalization's dynamics, ensuring their equitable participation and acknowledgment in societal development. AbstrakGlobalisasi menghadirkan tantangan yang kompleks bagi perempuan di seluruh dunia, menonjolkan bias gender dan mendorong pertanyaan tentang peran sosial mereka. Di Aceh, perempuan memegang posisi penting dalam mendorong kemajuan dan menjaga stabilitas sosial. Penelitian kualitatif ini menggunakan teknik survei deskriptif untuk menyelidiki status perempuan di Aceh. Penelitian ini terdiri dari berbagai tahap, termasuk pengumpulan data dari beragam informan, reduksi data, dan analisis. Temuan penelitian menggarisbawahi pentingnya mendefinisikan ulang persepsi tentang perempuan di Aceh dan merestrukturisasi hak-hak domestik dan publik mereka dengan sensitivitas. Bukti empiris menyoroti kontribusi signifikan perempuan Aceh terhadap kemajuan sosial, budaya, dan ekonomi di wilayah tersebut. Oleh karena itu, sangat penting untuk mengakui dan menghargai peran mereka di tengah dinamika globalisasi, untuk memastikan partisipasi dan pengakuan yang adil dalam pembangunan masyarakat.